Androgen Affects the Dynamics of Intrinsic Plasticity of Pyramidal Neurons in the CA1 Hippocampal Subfield in Adolescent Male Rats. (1st August 2020) - Islam, Md Nabiul; Sakimoto, Yuya; Jahan, Mir Rubayet; Ishida, Mako; Tarif, Abu Md Mamun; Nozaki, Kanako; Masumoto, Koh-hei; Yanai, Akie; Mitsushima, Dai; Shinoda, Koh
Highlights: The effects of androgen on the dynamics of intrinsic plasticity of CA1 pyramidal neurons in male rats were examined. Immunohistochemistry, Western blot and whole cell recording were performed using steroid-manipulated adolescent rat brains. Orchiectomy altered the dynamics of intrinsic plasticity and the effects were reversed by treatment with either T or DHT. Androgen receptor (AR)-antagonist treatment in intact rats resulted in changes similar to those in orchiectomized rats. These results suggest that androgen affects the excitability of CA1 pyramidal neurons, probably via activation of AR. Abstract: Androgen receptor (AR) is abundantly expressed in the preoptico-hypothalamic area, bed nucleus of stria terminalis, and medial amygdala of the brain where androgen plays an important role in regulating male sociosexual, emotional and aggressive behaviors. In addition to these brain regions, AR is also highly expressed in the hippocampus, suggesting that the hippocampus is another major target of androgenic modulation. It is known that androgen can modulate synaptic plasticity in the CA1 hippocampal subfield. However, to date, the effects of androgen on the intrinsic plasticity of hippocampal neurons have not been clearly elucidated. In this study, the effects of androgen on the expression of AR in the hippocampus and on the dynamics of intrinsic plasticity of CA1 pyramidal neurons were examined using immunohistochemistry, Western blotting and whole-cell current-clamp recording in unoperated, sham-operated, orchiectomized (OCX), OCX + testosterone (T) or OCX + dihydrotestosterone (DHT)-primed adolescent male rats. Orchiectomy significantly decreased AR-immunoreactivity, resting membrane potential, action potential numbers, afterhyperpolarization amplitude and membrane resistance, whereas it significantly increased action potential threshold and membrane capacitance. These effects were successfully reversed by treatment with either aromatizable androgen T or non-aromatizable androgen DHT. Furthermore, administration of the AR-antagonist flutamide in intact rats showed similar changes to those in OCX rats, suggesting that androgens affect the excitability of CA1 pyramidal neurons possibly by acting on the AR. Our current study potentially clarifies the role of androgen in enhancing the basal excitability of the CA1 pyramidal neurons, which may influence selective neuronal excitation/activation to modulate certain hippocampal functions.